Upaya Meningkatkan Keterampilan Teknik Dasar Senam Lantai Roll Depan Melalui Metode Demonstrasi pada Siswa Kelas 3A SD Negeri 015 Sumber Sari Kecamatan Tapung Hulu - Permana, Ande Agung; Makorohim, M. Fransazeli (Institut Teknologi Pendidikan Indonesia, 2023)
The purpose of this research was to determine the improvement of the basic technical skills of front roll floor gymnastics through the demonstration method for students of SD Negeri 015 Sumber Sari Kecamatan Tapung Hulu. The type of this research is PTK. The subjects of this study were 3rd-grade students at SD Negeri 015 Sumber Sari Kecamatan Tapung Hulu, totaling 27 people. The research instrument used was the front roll technique performance test. The data analysis technique used is to calculate the classical completeness scores achieved by students and the percentage of student category scores. From the results of this study, it can be concluded that there is an increase in forward roll through the variation method in students of SD Negeri 015 Sumber Sari Kecamatan Tapung Hulu with an average student skill score of 80.56, in the competent category with classical completenesspercentage of 85%.